2016
DOI: 10.1097/eja.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative shoulder pain after laparoscopic hysterectomy with deep neuromuscular blockade and low-pressure pneumoperitoneum

Abstract: Clinicaltrials.gov identifier: NCT01722097.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 19 publications
2
64
1
3
Order By: Relevance
“…In our view, the study by Madsen et al 1 does not reveal whether lower referred pain scores after laparoscopy should be attributed to the use of deep neuromuscular blockade, low-pressure pneumoperitoneum or a combination of both. In the discussion section, Madsen et al 1 state that their results were mainly because of the lower insufflation pressure, as there seems no rational explanation for an analgesic effect of deep neuromuscular blockade or sugammadex.…”
Section: Editormentioning
confidence: 58%
See 1 more Smart Citation
“…In our view, the study by Madsen et al 1 does not reveal whether lower referred pain scores after laparoscopy should be attributed to the use of deep neuromuscular blockade, low-pressure pneumoperitoneum or a combination of both. In the discussion section, Madsen et al 1 state that their results were mainly because of the lower insufflation pressure, as there seems no rational explanation for an analgesic effect of deep neuromuscular blockade or sugammadex.…”
Section: Editormentioning
confidence: 58%
“…In a recent issue of the European Journal of Anaesthesiology, Madsen et al 1 presented a randomised controlled trial, evaluating the effect of deep neuromuscular blockade and low-pressure pneumoperitoneum in laparoscopic hysterectomy. The authors concluded that deep neuromuscular blockade and low-pressure pneumoperitoneum (8 mmHg) reduced the incidence of postoperative shoulder pain as compared to standard pressure pneumoperitoneum (12 mmHg) with standard neuromuscular blockade.…”
Section: Editormentioning
confidence: 99%
“…Bogani and colleagues64 compared low-pressure (8 mm Hg) versus standard-pressure (12 mm Hg) pneumoperitoneum and found that while abdominal pain was similar between groups, the incidence of shoulder tip pain in the early postoperative period was 36% in the standard and 5% in the low-pressure group. Madsen and colleagues65 demonstrated less shoulder tip pain with lower inflation pressure. When carbon dioxide (CO 2 ) was humidified and heated, postoperative shoulder tip pain scores, but not abdominal pain scores, were lower than when using control gases 66.…”
Section: Resultsmentioning
confidence: 98%
“…A randomized trial in laparoscopic cholecystectomy with no versus deep neuromuscular blockade showed fewer sudden contractions and inadequate visibility with deep versus no neuromuscular blockade during the operation [5]. In a study in patients undergoing laparoscopic hysterectomy where they were randomized to moderate versus deep neuromuscular blockade, the overall findings were the same that the occurrence of sudden contractions in the diaphragm or lateral abdominal muscles, the occurrence of insufflator alarms, and increased abdominal wall tension were significantly more frequent in patients undergoing moderate versus deep neuromuscular blockade during surgery [6]. Thus, a deep neuromuscular blockade during laparoscopic procedures will impair muscle contractions and give a better workspace for the surgeon.…”
Section: Optimized Surgical Exposurementioning
confidence: 98%